Anti-inflammatory actions of plant-derived multiple monoclonal antibody CO17-1A × BR55 related with anti-cancer effects in AOM/DSS-induced colorectal cancer mouse via down-regulating of ERK1/2. Issue 4 (3rd July 2016) - Kwak, Dong Hoon; Heo, Sung Yun; Kim, Chang-Hyun; Kim, Ji-Su; Kim, Sun-Uk; Chang, Kyu-Tae; Choo, Young-Kug
ABSTRACT: Plant-derived multiple monoclonal antibody (mAb) CO17-1A × BR55 (mAb P CO17-1A × BR55) produced in transgenic tobacco plants were cross-pollinated with mAb CO17-1A and mAb BR55. Human anti-colorectal cancer multiple mAb CO17-1A × BR55 was cloned using pBI121 vector. Mice were given a single intraperitoneal injection of azoxymethane (AOM) with 10 mg/kg body weight. Starting 1 week after the injection, mice received 2% dextran sulfate sodium (DSS) in the drinking water for 1 week. In addition, the mice were injected intraperitoneal with mAbs dissolved in phosphate buffered saline (100 μg/mouse) twice per week for 4 weeks. Apoptotic cell death, expression of pro-apoptotic proteins, activity of inflammatory cytokines and ERK pathway phosphorylation were assayed by Western blot and TUNEL kit. mAb P CO17-1A × BR55 meaningfully and efficiently suppressed the development of AOM/DSS-induced colorectal inflammation and colorectal tumors, as determined by a reduced activation of inflammatory cytokines, number of colorectal tumor-induced mouse, number of tumor per mouse colon than other mAbs. Cell death by apoptosis was much increased in the mAb P CO17-1A × BR55-treated tumor compared with negative control. Apoptotic cell death and expression of pro-apoptotic proteins including Bax and cleaved caspase-3 were highest in treatment with mAb P CO17-1A × BR55. In addition, mAbP CO17-1A × BR55 was meaningfully decreased the expression of inflammatory cytokines, including COX-2, iNOS, p50 and p65, but the expression of PPARγ was significantly increased compared with AOM/DSS-induced carcinogenesis negative control. Moreover, mAb P CO17-1A × BR55 meaningfully repressed the ERK1/2 phosphorylation in AOM/DSS-induced colorectal tumors. Therefore, our results suggest that multiple mAb P CO17-1A × BR55 have meaningful effects of anti-inflammation related with the anti-carcinogenesis in AOM/DSS-induced colorectal tumor by inhibition of ERK1/2 phosphorylation.